Advances in earthquake prediction research and risk mitigation - Stefánsson, Ragnar (Springer Praxis Book, 2011)
The special natural conditions in Iceland as well as high level technology, were the basis for multidisciplinary and multinational cooperation for studying crustal processes, especially processes ahead of large earthquakes. This work leads to new innovative results and real time warnings which are described in the book. The results obtained in Iceland are of significance for earthquake prediction research worldwid